The Influence of Hospice-Palliative Nursing Knowledge, Empathy, and Attitude toward End-of-Life Care on Spiritual Care Competence of Nurses in Long-Term Care Hospital. - Hye Jin Lee; Mi Sook Park (Journal of Hospice & Palliative Care, 2025)
Purpose: This study was conducted to identify the influence of hospice·palliative nursing knowledge, empathy, and attitudes toward end-of-life care on spiritual care competence of nurses in long-term care hospitals. Methods: The participants was 174 nurses who had worked for more than one clinical year and experienced end-of-life care more than one time in 14 long-term-care hospitals in C province. Data were collected using questionnaires which consisted of hospice·palliative care knowledge, empathy, attitude toward end of life care, and spiritual care competence. Data were analyzed using the Statistical Package for the Social Science (SPSS) WIN 29.0 statistical program. Results: The job satisfaction, education level, empathy and attitude toward end-of-life care explained 36.9% of spiritual care competence and major predictor variable for spiritual care competence was attitude toward end-of-life care of nurse. Conclusion: Based on the results of this study, in order to improve the spiritual care competence of nurses in long-term care hospitals, it is necessary to consider education level among nurses and improve their job satisfaction. Also, in order to enhance their empathy and positive attitude toward end-of-life care, it is needed to develop and apply various systematic programs for nurses in long-term care hospitals.